2002
DOI: 10.1002/1099-0690(200206)2002:11<1745::aid-ejoc1745>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecamer 2,5-Dipropoxy-1,4-phenylenevinylene

Abstract: The conjugated, all‐(E)‐configured pentadecamer 2,5‐dipropoxy‐1,4‐phenylenevinylene 1j was prepared by a multistep synthesis on the basis of hydroquinone. The procedure consists of a general method for the repetitive extension of oligo(phenylenvinylene) chains by two styryl units (7a ⇄ 10 ⇄ 12 ⇄ 14). The relatively rigid oligomer 1j represents a molecular wire of about 100 Å. The absorption of 1j provides a proof for the convergence theory for electronic properties of conjugated oligomers with increasing numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…In this work, we show along with other investigators 3,8,[10][11][12][13][14][15]25 , that the overall response of the properties of π-conjugated compounds to donor-acceptor substitution can be expressed by means of simple analytical expressions. In earlier work 27 , we also showed that part of the response of a given property can be ascribed to substituent cooperative effects, i.e.…”
Section: The Substituent Cooperative Effect On the Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we show along with other investigators 3,8,[10][11][12][13][14][15]25 , that the overall response of the properties of π-conjugated compounds to donor-acceptor substitution can be expressed by means of simple analytical expressions. In earlier work 27 , we also showed that part of the response of a given property can be ascribed to substituent cooperative effects, i.e.…”
Section: The Substituent Cooperative Effect On the Propertiesmentioning
confidence: 99%
“…However, in the case of the 13 C NMR chemical shifts we notice only marginal effect. The strongest cooperative effects are observed for the D-PA-A and A-PA-A oligomers.…”
Section: 3 Cooperative Effect On the Chemical Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…11.1). The pentadecamer 2 ðn ¼ 15Þ, the highest known monodisperse OPV [2], has 8256 such conformers. Because of symmetry criteria, the number N is lower than 2 nÀ1 ¼ 2 14 ¼ 16384.…”
Section: Introductionmentioning
confidence: 99%